2009
DOI: 10.1111/j.1475-3995.2009.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Integer linear programming for a cutting problem in the wood‐processing industry: a case study

Abstract: In this paper, the authors present a case study from the wood‐processing industry. It focuses on a cutting process in which material from stock is cut down in order to provide the items required by the customers in the desired qualities, sizes, and quantities. In particular, two aspects make this cutting process special. Firstly, the cutting process is strongly interdependent, with a preceding handling process, which, consequently, cannot be planned independently. Secondly, if the trim loss is of a certain min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…O primeiro artigo que se refere ao problema de corte de estoque com as sobras aproveitáveis encontradas na literatura foi proposto por Brown em 1971 [3], mas somente posteriormente, esse problema foi abordado diretamente. Algumas abordagens de solução para PCESA podem ser encontradas em, Roodman [14], Scheithauer [15], Gradisar et al [9], Abuabara e Morabito [1], Nicola [12], Cherri et al [4], Koch et al [10], Cherri et al [5], Arenales et al [2] e entre outros.…”
Section: Introductionunclassified
“…O primeiro artigo que se refere ao problema de corte de estoque com as sobras aproveitáveis encontradas na literatura foi proposto por Brown em 1971 [3], mas somente posteriormente, esse problema foi abordado diretamente. Algumas abordagens de solução para PCESA podem ser encontradas em, Roodman [14], Scheithauer [15], Gradisar et al [9], Abuabara e Morabito [1], Nicola [12], Cherri et al [4], Koch et al [10], Cherri et al [5], Arenales et al [2] e entre outros.…”
Section: Introductionunclassified
“…Aiming to reduce operating costs, several aspects of the cutting process may be taken into account, and returning leftovers to stock so they can be used in future orders is one of them (see, for example, Koch et al. () and Chen et al. (), where the usage of leftovers in the wood‐processing and plastic‐film industries are considered).…”
Section: Introductionmentioning
confidence: 99%
“…One‐dimensional cutting/packing problems that allow the provision of residual pieces have been studied by different authors (Roodman, ; Scheithauer, ; Gradisar et al., , ; Sinuany‐Stern and Weiner, ; Gradisar and Trkman, ; Trkman and Gradisar, ; Cherri et al., , ; Dimitriadis and Kehris, ; Cui and Yang, ; Bang‐Jensen and Larsen, ). Examples of applications of one‐dimensional cutting problems with usable leftovers were reported in, for example, the textile industry (Gradisar et al., ), the agricultural light aircraft manufacturing (Abuabara and Morabito, ), and the wood‐processing industry (Koch et al., ). To the best of our knowledge, all studies reported in the literature focused on one‐dimensional residual bin‐packing problems, the exception being the recent published paper (Andrade et al., ) that deals with two‐dimensional nonguillotine cutting problems with usable leftovers.…”
Section: Introductionmentioning
confidence: 99%